Analisis Kinerja Bank BCA Syariah Menggunakan Metode Maqasid Syariah Index : Studi Kasus Bank BCA Syariah Tahun 2019-2023 - Anggraheni, Inawati Nur Erlita; Astuti, Evi Risdiyanti; Lestari , Novita; Vinia, Reines; Yuliminati, Ida (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
This study aims to analyze the performance of BCA Syariah Bank using the Maqasid Syariah Index approach. This method measures the performance of Islamic banks based on three main indicators, namely Education (Tahdzib Al-Fard), Upholding Justice (Al-'Adl), and Public Interest (Al-Mashlahah). These indicators are derived from the Maqasid Syariah concept, which is the main objective of Islamic sharia. The data used in this study are the financial statements and annual reports of BCA Syariah Bank for the 2019-2023 period. The results of this study provide insight into the performance of Bank BCA Syariah from a Maqasid Syariah perspective. They can act as a blend for bank management to formulate strategies and regulations that align with Islamic Sharia's objectives.